Synthesis of Ferrocenesulfonyl Chloride: Key Intermediate toward Ferrocenesulfonamides - Erb, William; Wen, Min; Roisnel, Thierry; Mongin, Florence (Synthesis, 2021)
Ferrocenesulfonyl chloride is the key intermediate in the synthesis of ferrocenesulfonamides, a family of underexplored derivatives. A one-pot synthesis of this compound, able to easily deliver multigram quantities of product, is reported. An original protocol for the synthesis of ferrocenesulfonamides is described along with highlighting the reactivity difference between arene and ferrocenesulfonyl chlorides. Finally, an example of diastereoselective deprotolithiation of chiral ferrocenesulfonamides is described.
Keywords: ferrocene; sulfonyl chloride; sulfonamide; scale-up; diastereoselective deprotolithiation